Rancang Bangun Sistem Robot Pemilah Sampah Anorganik dengan Inductive Proximity dan LDR Sebagai Sensor - Elfirza Rosiana; Rizki Perdana (Forum Kerjasama Pendidikan Tinggi, 2022)
The existence of garbage from day to day has always increased. In 2019, waste in Indonesia reached 98 million tons. Problems that arise because management of waste that is not done well, can hinder waste management. It is necessary to create a system that can sort waste according to its type so that the grouping of waste becomes more practical and the recycling process can be done easily. In this research, inorganic waste sorting robot was created that can be used as an automatic trash can that can sort and place inorganic waste according to its type. This system works by involving an inductive proximity sensor to detect metal waste and a light dependent resistor sensor equipped with a laser to detect metal waste, paper and plastic waste. From the results of testing on the tool, the accuracy of the detection of waste types for metal waste, paper waste and plastic waste is 84%, 88% and 90%, respectively. While the average response time of the non-organic waste sorting robot in detecting each type of waste is 2.15028 seconds for metal waste, 2.15014 seconds for paper waste and 2.15028 seconds for plastic waste